PEMBENTUKAN TEAMWORK DENGAN METODE OCAI (STUDI DESKRIPTIF PADA KARYAWAN PT XYZ PURWAKARTA) - Wida Ningsih; Tresna Wulandari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Referring to the years of service of PT XYZ employees, most of them have worked for 14.1 years. This shows that employees have high loyalty to the company. However, specifically for 2021, there are fluctuating customer complaints, and the most increased complaints occurred in June and November. This is due to the high employee turnover, so knowledge about the company's operational processes is less controlled. Meanwhile, the recruitment of new employees begins in April, so they are still in the adjustment stage in June and November. Especially since the Covid-19 pandemic, there has been an increase in demand for spare parts. Thus, limited knowledge and high employee turnover will affect the frequency of customer complaints, especially regarding product quality. The level of employee loyalty and turnover is one indicator that shows the quality of these employees when working in a team. This descriptive study aims to provide an overview of the formation of a work team at PT XYZ using the OCAI (Organizational Culture Assessment Instrument) approach or method. This activity is one of the stages of preparing the Balanced Scorecard as a strategic evaluation tool to measure the company's performance, especially from the perspective of growth and learning of the company's human resources. This study shows that the current dominant character with what employees expect is the same: a results-oriented company. However, the contemporary leadership style that employees expect is different, whereas the current leadership is more aggressive and focused on results. In contrast, what employees expect is leadership that is a mentor and facilitator who always provides guidance. The current condition of employees is also different from what is expected, where management is characterized by competitive, high-level, and results management, while what is expected is management characterized by teamwork, agreement/consensus, and participation. Different things are also found in the current company adhesive and what employees expect; where currently, the things that can unite the company are formal regulations and policies, while employees expect loyalty, commitment, and mutual trust as company glue. The emphasis of the company's current strategy on what employees expect is the same, namely emphasizing resilience and stability, efficiency and control, as well as smooth operation. The success criteria defined by the company today and what employees expect are the same, namely based on efficiency, reliable products and services, regular schedules, and low-cost production.